LANGUAGE AND IDENTITY OF VULNERABLE GROUP: TRACING THE ORIGINS OF THE TOBELO DALAM TRIBE FROM A LINGUISTIC PERSPECTIVE - Mahmud, Adi F.; Tamalene, M. Nasir (Lire Journal (Journal of Linguistics and Literature), 2025)
This study examines the complex relationship between language and identity within the Tobelo Dalam tribe, a semi-nomadic and socially marginalized community in North Halmahera, Indonesia. This research uses qualitative content analysis of ethnographic and linguistic literature to trace the beginnings of the Tobelo Dalam language and investigate its divergence from standard Tobelo. Essential findings indicate notable phonological, morphological, and syntactic differences alongside preserved archaic Austronesian vocabulary, implying linguistic independence influenced by ecological seclusion and oral customs. Concurrently, common grammatical characteristics and ethnobotanical lexicon corroborate cultural and linguistic continuity. These dynamics underscore a dual process of distinction and convergence that defines the group's evolving identity. The research determines that Tobelo Dalam should be considered a unique language and cultural entity. It promotes the immediate implementation of micro-level documentation and inclusive language policies that honour Indigenous self-determination. The results enhance discussions on language endangerment, cultural resilience, and the necessity for decolonial approaches in linguistic anthropology.